EVALUATION OF MEMBRANE INTEGRITY OF BULL FROZENTHAWED SPERM USING WATER AND HYPO OSMOTIC SWELLING TEST - Godratollah Mohammadi; Hamed Mahdion (Basrah Journal of Veterinary Research)
Assessment of the sperm membrane functional status appears to be a significant marker for the fertilizing capacity of spermatozoa. The hypo osmotic swelling test (HOST) is one of the best methods to evaluate sperm membrane integrity. In the current study, we used DW and hypo osmotic solutions of 50 and 100mOsm/l of dextrose/NaCl, NaCl, sucrose and fructose. Based on the results, Among the dextrose/NaCl, NaCl, sucrose, and fructose solutions and DW, Maximum numbers of swollen of bull frozen-thawed spermatozoa were observed with DW and dextrose/NaCl solution at 50 mOsm with average response by 61.20±8.677 and 47.90±10.181 respectively. The HOST response at 3 and 60 min for all of solutions were positively correlated to each other and there was no significant difference between the responses to the HOST at 3 and 60 min after incubation in all of solutions. The significant correlation was observed between motility and dextrose/NaCl at 50 mOsm, sucrose 50 and 100 mOsm, NaCl 50 mOsm and DW. The high relationship was between motility and DW and dextrose/NaCl at 50 mosm. There was no significant correlation between DW and all of hypoosmotic solutions with staining of the spermatozoa by eosin/nigrosin. In conclusion, the water test can be efficiently used for the evaluation of the functional integrity of the plasma membrane of bull frozen-thawed spermatozoa. The hypoosmular solution of dextrose/NaCl at 50 mOsm is a good medium to evaluate bull frozen spermatozoa. The used of HOST and motility are better tests to evaluate bull frozen thawed sperm than eosin-nigrosin. The short HOST procedure (3 min) is suitable method for evaluating of membrane integrity of bull frozen/thawed spermatozoa